THE EFFECT OF EXTRACT OF DATE PALM FRUIT (PHOENIX DACTYLIFERA L.) ON FERTILITY IN MALE MICE (MUS MUSCULUS L.) - Dillasamola, Dwisari; A, Almahdy; Elfianita, Feni; Diliarosta, Skunda; Oktomalio P, Biomechy; Noverial, Noverial (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Date palm is one of the plants that have used empirically to increase fertility. Ethanol induction can cause sperm damage in male mice. Sperm damage is one of the infertility agents. The aim of this study was to observe and determine anti-infertility effects of the ethanol extract of date palm fruit in khalal stage in male mice compared with propolis. Methods: A total of 5 groups were assigned to 1 control and 4 experimental groups. Control group was treated by intraperitoneal administration of ethanol only. Meanwhile, experimental groups was treated by intraperitoneal administration of ethanol induction and oral administration of 140, 280, and 560 mg/kg BW of khalal date fruit extract and 1400 mg/kg BW of propolis for 34 days. At 35th day, the mice were deeply anesthetized with anesthetic ether and sacrificed. Laparotomy was performed to collect sperms from epididymis and testes for determining testis weight to analyze the sperm. The data were analyzed using one-way ANOVA and Duncan's test. Results: The result of the research showed that there were anti-infertility activity of ethanol extract of date palm fruit in khalal stage (p<0.05) on count, motility of sperm and weight of testes in male white mice toghether with larger doses administration. The optimum activity was accepted by the administration of doses 560 mg/kg BW. Conclusion: Ethanol extract of khalal date fruit and propolis can increase the quality of sperm pervade sperm count, sperm motility, and weight of testes. Ethanol extract of khalal date fruit can increase sperm quality higher than propolis.